AFFECT IN COMMENTS ON SENSUAL CONTENT ON SOCIAL MEDIA X: AN APPRAISAL STUDY - Isyroof Rizq Zaftika; T Kasa Rullah Adha; Muhammad Yusuf (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2026)
Social media is now a means of communication, information search, and interaction. One of the most widely used platforms is social media X. On this platform, users can not only share information but also freely upload various types of content, including photos and videos. The content published is also very diverse, ranging from general topics to explicit content, including vulgar and even pornographic material, without any strict restrictions from the platform. One example is the X social media account of June Liu, an adult actress from China with more than 1.7 million followers, making her one of the most influential figures in the digital world. Through this platform, users can participate in discussions by commenting on each post. In these interactions, affective expressions often appear, reflecting a wide range of emotions, both positive ones that show appreciation or pleasant emotional responses and negative ones that show dislike or unpleasant emotional responses. Affect itself is one of the components in the Appraisal system that refers to the expression of emotions in language, either directly or indirectly. In this study, data in the form of Mandarin comments were collected using purposive sampling and analysed using content analysis. The results of the study show that two types of affect emerge, namely: (1) positive affect with the categories of happiness, security, and satisfaction, and (2) negative affect with the category of dissatisfaction.